Determination of Anabolic Hormones in Porcine Hair by High-Performance Liquid Chromatography–Mass Spectrometry. (11th December 2016) - Li, Yanqin; Yu, Pengling; Wang, Qin; Zhou, Qiaoyi; He, Limin; Yang, Haicui; Fang, Binghu
ABSTRACT: A sensitive, rapid, efficient, and reliable method is reported for the determination of testosterone, 17α-methyltestosterone, trenbolone, trenbolone acetate, boldenone, nandrolone phenylpropionate, nandrolone, and norethindrone in porcine hair. This protocol involves treating 100 mg of pulverized hair by mild digestion using tris(2-carboxyethyl)phosphine hydrochloride and subsequent extraction of the anabolic hormones with methyl tert -butyl ether. The separation of the analytes was performed using acetonitrile and 0.1% aqueous formic acid. Quantitative analysis was performed by high-performance liquid chromatography–tandem triple-quadrupole mass spectrometry with positive electrospray ionization. This method is accurate, offers good sensitivity and high recovery, allowing the determination of anabolic hormones in porcine hair.